Espaço de fazer saberes: um estudo das interfaces da arte e do conhecimento popular - Joice Saturnino de Oliveira (2015)
This thesis presents a work developed in a particular geographic territory for the study within the Sertão Mineiro, corresponding to the northern mesoregion and of the northwest region of Minas Gerais State, where oral tradition is revealing of knowledge and expertise that have progressed in everyday practices, allowing memories and reflections materialize through a creative process that moves between popular culture and the exchange of artistic experiences. Therefore, the relationships among cultures, history, space and knowledge gathered by this population create the reference identity of each local. Processes rarely worked in traditional schools that will dialogue with the world of knowledge acquired through their studies and documentary sources. It is established a process of transformation of oral sources in scientific knowledge where the importance of popular culture and its rightful place is set. The focus of this work is the recovery and the reapropriation of the traditional wisdom and the creative process that transits through the places, images and people, where knowledge and experiences are an integral part of the main body. The approach will be guided by three points. Studies of the place of output which are based on the creative process, sources, the acquired knowledge, their interrelationships and the symbolic and cultural exchanges of the sites of the research: the Sertão Mineiro selected by the dialogue with the urban space here represented by the University. The oral histories that are the sources used and the issue of knowledge that points out the route which propitiated the journey and wisdom acquired. The meeting, finally, with the people that maintain the local tradition. The creative process that focuses on the construction of an artistic proposal, anchoring on the outcome of the process carried out by the study which is revealed in a plastic alternative. The art object.